163 Frailty, Doesn't That Mean Birdlike? Research Into Attitudes and Understanding of Frailty in Undergraduate and Postgraduate Trainees. (16th March 2021) - Hartley, S; Cropp, A; Fisher, J
Abstract: Introduction: Frailty is an increasingly recognised concept, with 25–50% of over 85's estimated to be frail1, . Previous research considered medical students' attitudes towards older people2, yet despite the correlation between frailty and increased age3, little is known about attitudes of healthcare professionals towards frailty. We researched attitudes towards, and understanding of, frailty in undergraduate and postgraduate trainees, with a view to guiding future educational interventions. Method: Approval was granted by Northumbria Healthcare NHS Foundation Trust (NHCT) Research and Development department, Newcastle University's Research Management Group and the HRA. 3 cohorts were recruited; 3rd year Newcastle University MBBS Students, 5th year Newcastle University MBBS Students and Foundation Year 2 and Core Medical Trainees working for NHCT (junior doctors). Data was collected during scheduled teaching at NHCT and individuals were invited to participate via email prior to this. Those not participating were still required to attend the teaching. Participants provided written consent. Within each cohort, small group discussions around frailty and Comprehensive Geriatric Assessment (CGA) were prompted using open questions (e.g. "what does frailty mean to you?"), during which participants anonymously submitted phrases to an online word-cloud generator. Discussions were audio recorded and transcribed. Transcriptions and word-clouds were analysed using Simple Content Analysis. The over-arching themes within each cohort were identified and compared with other cohorts. Interpretations were reviewed by an independent researcher to enhance rigour. Results: Each cohort associated frailty with older age and weakness, and often used it as a byword for complexity. Frailty was described as an abstract construct composed of personal experiences rather than an objectively defined descriptor. All associated it with negative emotions. Cohorts differed in their approach, with 3rd year students primarily focussed on defining frailty, whereas junior doctors prioritised the clinical challenges it presented. Junior doctors demonstrated limited understanding of CGA whilst undergraduate students were almost universally ignorant of it. Conclusions: The lack of understanding around frailty and CGA is concerning given its high prevalence. The identification of negative emotions increases this concern. To challenge this, focussed educational interventions addressing understanding and attitudes ought to be developed for tomorrow's doctors. References: 1. Clegg et al. Lancet 2013; 381: 752–62. 2. Samra et al. Age Ageing 2017; 46: 911–9. 3. Romero-Ortuno et al. Age Ageing 2012; 41: 684–9.